Duplicate publication: a growing challenge - Reza Negarandeh (Tehran University of Medical Sciences, 2013)
During several years of cooperation with scientific journals in Iran as referee, member ofeditorial boards and editor in chief, I have faced with multiple non-ethical behaviors inpublication. These days, I am witnessed to submitting articles to two or more journalsimultaneously. Due to the growing pattern of this illegal action, this editorial will assess itsdimensions and consequences.The Article 1, Chapter VI of the National guidelines on Ethics of Publishing MedicalResearch has clearly stated: "If a manuscript is published or is being considered for publicationin print or electronically, re-publishing in or submitting to other journals is not allowed. Thisstatement is so important that the editors of the scientific journals have mentioned it in theauthor guidelines of the journals. However, what make authors, especially beginners, to submittheir articles to more than one journal are perhaps requirements of the Institutes for defending athesis, annual and/or academic ranks promotions.Republishing articles in scientific journals, especially in the same language, result inspending cost and taking time of the scientific and executive teams of the Journals and has noadded value. The negative effects of this action are more highlighted when the role of scientificjournals in promoting health care quality through publishing new and valid scientific evidencesand limited spaces of the journals are noticed.